2003
DOI: 10.1016/s1389-0344(03)00067-4
|View full text |Cite
|
Sign up to set email alerts
|

Potent antibacterial activity of halogenated metabolites from Malaysian red algae, Laurencia majuscula (Rhodomelaceae, Ceramiales)

Abstract: Red algae genus Laurencia (Rhodomelaceae, Ceramiales) are known to produce a wide range of chemically interesting secondary halogenated metabolites. This investigation delves upon extraction, isolation, structural elucidation and antibacterial activity of inherently available secondary metabolites of Laurencia majuscula Harvey collected from two locations in waters of Sabah, Malaysia. Two major halogenated compounds, identified as elatol (1) and iso-obtusol (2) were isolated. Structures of these compounds were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
78
0
6

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(87 citation statements)
references
References 12 publications
3
78
0
6
Order By: Relevance
“…Our result is in accordance with the antibacterial activity of Laurencia spp. reported from various geographic regions (DE NYS et al 1996, HELLIO et al 2001, TASKIN et al 2007) against marine, human and fish bacterial pathogens (VAIRAPPAN et al 2001(VAIRAPPAN et al , 2003BANSEMIR et al 2006). Based on the present findings L. brandenii could be utilized as renewable bioresource for the development of potential antimicrobials.…”
Section: Discussionsupporting
confidence: 64%
“…Our result is in accordance with the antibacterial activity of Laurencia spp. reported from various geographic regions (DE NYS et al 1996, HELLIO et al 2001, TASKIN et al 2007) against marine, human and fish bacterial pathogens (VAIRAPPAN et al 2001(VAIRAPPAN et al , 2003BANSEMIR et al 2006). Based on the present findings L. brandenii could be utilized as renewable bioresource for the development of potential antimicrobials.…”
Section: Discussionsupporting
confidence: 64%
“…The potency observed was as good as or better than six standard, commercial available antibiotics (augmentin, latamoxef, ceflaclor, ceftriaxone, kanamycin, and netilmicin). 504 In the same study, iso-obtusol (64) exhibited antibacterial activity against four bacteria with especially noteworthy activities against K. pneumoniae and Salmonella sp. 504 Further experiments demonstrated that both compounds displayed bacteriostatic rather than bactericidal effects.…”
Section: Biological Activitiesmentioning
confidence: 88%
“…504 Further experiments demonstrated that both compounds displayed bacteriostatic rather than bactericidal effects. 504 While brominated diterpene 10-acetoxyangasiol (289) exhibited antibacterial activity against Vibrio cholerae with MIC 100 μg/mL, 194 the bromoditerpene 10-hydroxykahukuene B (341) displayed weak antibacterial activity against Staphylococcus aureus, and this compound as well as the ACG derivative laurenmariallene (433) exhibited weak activity against Escherichia coli. 67 Recently, ACG derivatives 455 and 458−460 were reported to have antistaphylococcal activity against a panel of multidrug and methicillin-resistant S. aureus strains with MICs ranging from 8 to 256 μg/mL.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…Lamouroux (Ceramiales, Rhodomelaceae), have proven to be a prolifi c source of secondary metabolites and have been the subject of intensive research in the fi eld of marine natural products (Faulkner, 2000;Guaratini et al, 2005;Cardozo et al, 2006;Cardozo et al, 2007). Many of Laurencia's metabolites have been found to possess a variety of biological activities such as antibacterial (Vairappan, 2003;Kladi et al, 2008;Vairappan et al, 2008), cytotoxic (Kladi et al, 2006;Kladi et al, 2007;Cen-Pacheco et al, 2011;Lhullier et al, 2010), antioxidant (Li et al, 2009), antimalarial (Topcufold with ethyl acetate prior to analysis by GC-MS.…”
Section: Introductionmentioning
confidence: 99%